Barrett's oesophagus and oesophageal adenocarcinoma: how does acid interfere with cell proliferation and differentiation?. (11th February 2005) - Fitzgerald, R C
Abstract : Acid, a principal component of gastro-oesophageal refluxate, may contribute to the development and malignant progression of Barrett's oesophagus. Oesophageal pH monitoring studies have demonstrated that patients with Barrett's oesophagus have severe and chronic acid reflux. However, there is overlap between the amount of acid exposure in patients with oesophagitis compared with patients with Barrett's oesophagus. This suggests that factors other than acid may be important in the aberrant oesophageal cell differentiation process that leads to the development of the metaplastic Barrett's mucosa. The other factors important in the aetiology of Barrett's oesophagus are poorly understood but probably include both genetic and environmental factors.